2018
DOI: 10.1186/s13058-018-1037-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-PD-1-based therapy against triple-negative breast cancer patient-derived xenograft tumors engrafted in humanized mouse models

Abstract: BackgroundBreast cancer has been considered not highly immunogenic, and few patients benefit from current immunotherapies. However, new strategies are aimed at changing this paradigm. In the present study, we examined the in vivo activity of a humanized anti-programmed cell death protein 1 (anti-PD-1) antibody against triple-negative breast cancer (TNBC) patient-derived xenograft (PDX) tumor models.MethodsTo circumvent some of the limitations posed by the lack of appropriate animal models in preclinical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 72 publications
1
81
0
Order By: Relevance
“…3 6 Despite this, the use of antibodies against PD-1 has shown efficacy in human xenograft and patient-derived xenograft tumors in these mice, demonstrating that these cells can generate antitumor responses. [7][8][9][10] Whereas checkpoint modulators have shown antitumor activity in humanized mice, there are limited data reporting characterization on human immune cell subsets within these tumors. To this end, we characterized several commonly used xenograft models across a range of tumor types in CD34 + humanized non-obese diabetic-scid gamma (NSG) mice.…”
Section: Introductionmentioning
confidence: 99%
“…3 6 Despite this, the use of antibodies against PD-1 has shown efficacy in human xenograft and patient-derived xenograft tumors in these mice, demonstrating that these cells can generate antitumor responses. [7][8][9][10] Whereas checkpoint modulators have shown antitumor activity in humanized mice, there are limited data reporting characterization on human immune cell subsets within these tumors. To this end, we characterized several commonly used xenograft models across a range of tumor types in CD34 + humanized non-obese diabetic-scid gamma (NSG) mice.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse xenograft studies are one of the cornerstones of modern cancer research where human tumour cells are typically grafted into a mouse host either subcutaneously or orthotopically as a means to evaluate oncogene and tumour suppressor gene function or investigate the therapeutic effects of drugs [28, 29]. In these models, there are complex interactions between the human tumour cells and the host microenvironment which play important roles in driving cancer progression and therapy response [3032].…”
Section: Resultsmentioning
confidence: 99%
“…Drawbacks for the use of PDXs include the selection of more aggressive cells within the patient sample and the use of immunocompromised mice to prevent tumor rejection. Developing mice with humanized immune systems can help to address this problem (Hasgur et al, 2016), as recently shown for a metastasis model (Rosato et al, 2018) (Figure 1D).…”
Section: Patient-derived Xenografts (Pdxs)mentioning
confidence: 88%